2000
DOI: 10.1161/01.cir.101.9.969
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction Complicated by Atrial Fibrillation in the Elderly

Abstract: Background-Although atrial fibrillation (AF) is a common complication of acute myocardial infarction (MI), patient characteristics and association with outcomes remain poorly defined in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
193
3
12

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 304 publications
(231 citation statements)
references
References 23 publications
23
193
3
12
Order By: Relevance
“…1 -4 The most important underlying mechanism producing the new-onset AF is hemodynamic disturbance imposed by AMI. 5 The occurrence of new-onset AF reflects a poor clinical profile suggesting higher risk in patients with AMI. 2 -8 Mostly, newonset AF in its paroxysmal form complicates AMI, 1,8 and it may be recurrent in the postinfarction period.…”
Section: Introductionmentioning
confidence: 99%
“…1 -4 The most important underlying mechanism producing the new-onset AF is hemodynamic disturbance imposed by AMI. 5 The occurrence of new-onset AF reflects a poor clinical profile suggesting higher risk in patients with AMI. 2 -8 Mostly, newonset AF in its paroxysmal form complicates AMI, 1,8 and it may be recurrent in the postinfarction period.…”
Section: Introductionmentioning
confidence: 99%
“…AF is an important comorbidity in ACS. Most recent studies have demonstrated that AF is associated with a higher risk of subsequent cardiovascular events33 and mortality12 in ACS. Thus, both ECG variables (ie, QTc prolongation) and AF are predictors of adverse outcomes in patients with ACS.…”
Section: Discussionmentioning
confidence: 99%
“…23 The prevalence of AF in AMI ranges from 2% to 21%, 23 and this arrhythmia not only increases in-hospital mortality 24,25 but also worsens long-term outcome after discharge. 24 In turn, the accurate data on the prevalence of AF in an unselected population of patients with stable CAD are not available.…”
Section: -20mentioning
confidence: 99%